Promotion of «Soft Power» of Russia in Central Asia as an Instrument of Development of the Eurasian Economic Integration - Andrey Anatolyevich Kazantsev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article says that it is very important to promote the «soft power» of Russia in Central Asia for the development of the Eurasian economic integration. In this regard, the authors demonstrate on some cases that at present soft power plays an important role in the practice of the regional policy of the great powers in the region. The article points out that now Russia has developed and practically controls an extensive system of soft power instruments guaranteeing multilateral cooperation in the social and humanitarian sphere. The authors analyze application of soft power in specific areas and define the shortcomings of Russian soft power that must be addressed for the effective application of this instrument in the world in general and in Central Asia in particular. At the end, some practical conclusions and recommendations are made.